Orientational Coupling Locally Orchestrates a Cell Migration Pattern for Re-Epithelialization - Hu, Benhui (2017)
Re-epithelialization by collective migration of epithelial cells over a heterogeneous environment to restore tissue integrity and functions is critical for development and regeneration. Here, it is reported that the spatial organization of adjacent adherent paths within sparsely distributed extracellular matrix (ECM) has a significant impact on the orientational coupling between cell polarization and collective cell migration. This coupling effect determines the migration pattern for human keratinocytes to regain their cohesion, which impacts the occupancy of epithelial bridge and the migration velocity in wound repair. Statistical studies suggest the converging organization of ECM, in which adjacent paths become closer to each other and finally converge to a junctional point, facilitating collective cell migration mostly within variable ECM organization, as the polarization of the advancing cell sheet is remodeled to align along the direction of cell migration. The findings may help to design implantable ECM to optimize efficient skin regeneration.